Cell Junctions in Periodontal Health and Disease: An Insight - Puzhankara, Lakshmi; Rajagopal, Anjale; Kedlaya, Madhurya N.; Karmakar, Shaswata; Nayak, Namratha; Shanmugasundaram, Shashikiran (European Journal of Dentistry, 2023)
Cells are the building blocks of all living organisms. The presence of cell junctions such as tight junctions, gap junctions, and anchoring junctions between cells play a role in cell-to-cell communication in periodontal health and disease. A literature search was done in Scopus, PubMed, and Web of Science to gather information about the effect of cell junctions on periodontal health and disease. The presence of tight junction in the oral cavity helps in cell-to-cell adhesiveness and assists in the barrier function. The gap junctions help in controlling growth and development and in the cell signaling process. The presence of desmosomes and hemidesmosomes as anchoring junctions aid in mechanical strength and tissue integrity. Periodontitis is a biofilm-induced disease leading to the destruction of the supporting structures of the tooth. The structures of the periodontium possess multiple cell junctions that play a significant role in periodontal health and disease as well as periodontal tissue healing. This review article provides an insight into the role of cell junctions in periodontal disease and health, and offers concepts for development of therapeutic strategies through manipulation of cell junctions.
Keywords: anchoring junctions; desmosomes; gap junctions; hemidesmosomes; tight junctions